6+9(x-7)=7-8(x-7)

Simple and best practice solution for 6+9(x-7)=7-8(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+9(x-7)=7-8(x-7) equation:


Simplifying
6 + 9(x + -7) = 7 + -8(x + -7)

Reorder the terms:
6 + 9(-7 + x) = 7 + -8(x + -7)
6 + (-7 * 9 + x * 9) = 7 + -8(x + -7)
6 + (-63 + 9x) = 7 + -8(x + -7)

Combine like terms: 6 + -63 = -57
-57 + 9x = 7 + -8(x + -7)

Reorder the terms:
-57 + 9x = 7 + -8(-7 + x)
-57 + 9x = 7 + (-7 * -8 + x * -8)
-57 + 9x = 7 + (56 + -8x)

Combine like terms: 7 + 56 = 63
-57 + 9x = 63 + -8x

Solving
-57 + 9x = 63 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-57 + 9x + 8x = 63 + -8x + 8x

Combine like terms: 9x + 8x = 17x
-57 + 17x = 63 + -8x + 8x

Combine like terms: -8x + 8x = 0
-57 + 17x = 63 + 0
-57 + 17x = 63

Add '57' to each side of the equation.
-57 + 57 + 17x = 63 + 57

Combine like terms: -57 + 57 = 0
0 + 17x = 63 + 57
17x = 63 + 57

Combine like terms: 63 + 57 = 120
17x = 120

Divide each side by '17'.
x = 7.058823529

Simplifying
x = 7.058823529

See similar equations:

| 3x-108=11x+124 | | -6p+35=11 | | -36+11x=7x+44 | | -2x+19x=0 | | 5(6z-1)-3(z+1)=4(z+1) | | 5w-15=15 | | 0.09Xx=134.38 | | 2x+19x=0 | | 9+r+2r=r+1+4 | | (y+1)(y+2)=30 | | y/9-7=9 | | -25+5x=27+9x | | 13x-21=29+3x | | 12y-1=14t-5 | | 20x+3y=175 | | y/9-7-9 | | B/915 | | 110=12+6t | | 6-(2x-1)=5(3x-4) | | 6+3k=6+2k | | 30x+35y=58450 | | -9/8=8/1 | | y=-3.8x+4.8 | | w-2(8-w)=31 | | 106=4r+2d | | 2x-19+1=0 | | 30x+35y=49233 | | 0=36x^2+12x-6 | | 2x-2.19=0 | | 6x-2=-3 | | 5(2x-1)+6=5(x+2)-9 | | 2(5t-2)=-4[2t+5(t-10)] |

Equations solver categories